2012
DOI: 10.1007/s10228-012-0306-y
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition in summer of rosefish Helicolenus hilgendorfii on the southeastern coast of Korea

Abstract: The feeding habits of Helicolenus hilgendorfii were studied using 93 specimens (35-135 mm in standard length) collected from the southeastern coast of Korea during the summer season (June-August) from 2005 to 2007. Helicolenus hilgendorfii is a carnivore that mainly consumes shrimps and fishes. Its diet also includes small quantities of mysids, amphipods, euphausiids, copepods, and isopods. Our graphical method for feeding habits revealed that H. hilgendorfii is an opportunistic and specialized predator on shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Similar size-related changes in diet have been documented in other scorpaenid species. For example, Harmelin-Vivien et al (1989) found that juveniles of Scorpaena species feed mainly on small crustaceans and amphipods, while the larger adult fish ingest teleosts and decapods, with other species in the Sebastidae and Platycephalidae also showing this pattern (Baeck et al, 2013;Blaber & Bulman, 1987;Hashemi & Taghavi Motlagh, 2013;. The shift to larger prey probably reflects morphological and maturational changes such as an increased mouth gape, as well as improved locomotory and sensory abilities, resulting in an increase in the ability of larger N. pandus to capture and ingest larger, more mobile prey (Consoli et al, 2010;Gerking, 1994;Keenleyside, 1979;Wootton, 1998).…”
Section: Size-related Changes In Dietary Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar size-related changes in diet have been documented in other scorpaenid species. For example, Harmelin-Vivien et al (1989) found that juveniles of Scorpaena species feed mainly on small crustaceans and amphipods, while the larger adult fish ingest teleosts and decapods, with other species in the Sebastidae and Platycephalidae also showing this pattern (Baeck et al, 2013;Blaber & Bulman, 1987;Hashemi & Taghavi Motlagh, 2013;. The shift to larger prey probably reflects morphological and maturational changes such as an increased mouth gape, as well as improved locomotory and sensory abilities, resulting in an increase in the ability of larger N. pandus to capture and ingest larger, more mobile prey (Consoli et al, 2010;Gerking, 1994;Keenleyside, 1979;Wootton, 1998).…”
Section: Size-related Changes In Dietary Compositionmentioning
confidence: 99%
“…Of the two studies of neosebastids, Maxillicosta scabriceps Whitley 1935 ate mainly large crustaceans, while 50% of the diet of Neosebastes scorpaenoides Guichenot 1867 comprised large crustaceans, with small crustaceans, gastropods and teleosts constituting the remaining portions (Bulman et al, 2001;Platell & Potter, 2001). As some sebastid and scorpaenid species increase in size, their diets shift from mainly crustaceans to primarily fish (Baeck et al, 2013;Harmelin-Vivien & Bouchon, 1976;Murie, 1995;Neves et al, 2011).…”
mentioning
confidence: 99%